2021
DOI: 10.3390/ijms222111628
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Lymphangiogenesis: Current Pathophysiological Understandings and Its Functional Role in Ocular Surface Disease

Abstract: The cornea is a transparent and avascular tissue that plays a central role in light refraction and provides a physical barrier to the external environment. Corneal avascularity is a unique histological feature that distinguishes it from the other parts of the body. Functionally, corneal immune privilege critically relies on corneal avascularity. Corneal lymphangiogenesis is now recognized as a general pathological feature in many pathologies, including dry eye disease (DED), corneal allograft rejection, ocular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 119 publications
0
19
0
Order By: Relevance
“…6 HS has been associated with absent neck holding and webbed neck. 1,23,24,44,45 Our patient sat sideways in a wheelchair, his face turned downwards and to the left, looking at his mother throughout his clinical encounter. Our patient's asymmetrical cervical muscle tone could be due to the absence of neck holding reported in HS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 HS has been associated with absent neck holding and webbed neck. 1,23,24,44,45 Our patient sat sideways in a wheelchair, his face turned downwards and to the left, looking at his mother throughout his clinical encounter. Our patient's asymmetrical cervical muscle tone could be due to the absence of neck holding reported in HS.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 HS has also been associated with limb deformities. 1,2,22,23,24 Our patient had long-standing established care with a podiatrist prior to his chief complaint clinic visit. He reported that he had been unable to wear shoes for many years because of swelling episodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key molecule involved in pathogenic corneal neovascularization is VEGF [ 80 ]. Expression of VEGF has been attributed to stimulation by inflammatory cytokines, notably interleukins-1,6 and tumor necrosis factor-alpha (IL-1, IL-6, TNF-α) [ 81 , 82 , 83 ]. Interestingly in some pathologies, corneal neovascularization occurs in parallel with epithelial hyperplasia, disruption of the Bowman layer, disorganized stromal collagen fibers and fibroblast activation [ 4 ].…”
Section: The Wound Healing Processmentioning
confidence: 99%
“…This process is accelerated when the injury is superficial such as with most corneal abrasions that heal without any complications [ 4 , 86 ]. Stem cells and, in particular, progenitor cells such as the transient amplifying cells of the limbal epithelium contribute to the rapid healing [ 82 , 86 , 87 , 88 ]. Corneal epithelial wound healing involves several key phases: adhesion of the ingrowing cells to the BM, migration to cover the wound, cell proliferation and differentiation [ 87 , 89 , 90 ].…”
Section: The Wound Healing Processmentioning
confidence: 99%